How psychological ownership is prevented in non-family employees in family firms (Singapore) - Teo, Benjamin Keng Meng (2021)
Family firms or businesses are often regarded as the backbone of the national economy. They contribute to majority of the world’s gross domestic product and provides almost half of the jobs in most countries. Family firms typically employs more non-family employees compared to family employees.